Dermatitis artefacta in the patients of obsessive compulsive disorder: A case series - Arijit Mondal; Ranjan Das; Abhijit Chattopadhyay; Soumi Ghosh (Annals of Indian Psychiatry, 2023)
Dermatitis artefacta or factitious dermatitis is a psychodermatological disorder commonly found in dermatology and psychiatric departments. Comorbid psychiatric disorders are frequently seen with this conditions and proper meticulous history and evaluation both from dermatology and psychiatric point of view is needed to make this diagnosis of exclusion. There are no definite diagnostic criteria or treatment protocols for the above conditions and a combination of psychiatric dermatological and psychological approach is needed to manage this. Lack of proper clinical knowledge and awareness regarding the condition may lead to misdiagnosed the cases frequently. Here we have reported the three cases of dermatitis artefacta with comorbid obsessive compulsive disorder.